FACILITATING COMPLEX THINKING IN EDUCATIONAL PSYCHOLOGY(The Perspectives of Kelvin Seifert and Rosemary Sutton) - Muhammad Nur; Anisaurrohmah; Mahmud Fauzi Hamidy (CV. ADIBA AISHA AMIRA, 2021)
Teaching involves a variety of instructional strategies, where decisions and actions are designed to facilitate learning. The choice of strategy depends in part on the forms of thinking aimed at the student-whether the goal is for students to think critically, for example, or to think creatively, or to solve problems